RESPON SISWA TERHADAP PENERAPAN PEMBELAJARAN INKUIRI TERSTRUKTUR DI KELAS VII PADA MATERI KEANEKARAGAMAN HAYATI INDONESIA - Shaumuristi, Shendy Shafna (MEDIA DIDAKTIKA, 2024)
This study aims to describe students' responses to the application of learning that has been carried out in class using a structured inquiry learning model. The data collection technique used was the survey method by distributing student response questionnaires. The data analysis technique uses a Likert scale which is categorized under several criteria. The subjects in this study were 16 students in class VII-D of SMP Negeri 5 Lamongan. The results of this study showed that overall students gave a positive response, seen from the average percentage of each student above 76%, including the very good category.